Analysis of the Disclosure of Islamic Social Reporting Index At Sharia Banking in Indonesia - Febriyanti, Novi; Ihsani, Fikri Amiruddin; Bustamir, Aidil (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The purpose of this study was to determine and analyze the Islamic Social Reporting Index at Islamic banks and the Islamic Social Reporting Index at Bank Syariah Indonesia (BSI). The method used in this study is a qualitative approach through interviews and content analysis. The subject of this research is the Islamic Social Reporting Index. The object used in this research is the publication report of Bank Syariah Indonesia (BSI). The Islamic Social Reporting Index items used in this study amounted to 50 items, covering 6 themes including investment and finance, products and services, employees, social, environment, and organizational governance. The results of the analysis of the Islamic Social Reporting Index in the annual report show that there are 43 items that are in accordance with the Islamic Social Reporting Index. The percentage of Islamic Social Reporting Index obtained by Bank Syariah Indonesia (BSI) is 86%. This shows that Bank Syariah Indonesia (BSI) in the disclosure of social responsibility reports is in accordance with sharia values. From the results of this study, it is expected that the Financial Services Authority will make rules for Islamic banks in presenting their annual reports.